The Correlation Between Erythrocyte Sedimentation Rate (ESR) and Platelet Count with Fever Levels in Pediatric Patients with Typhoid Fever at Methodist General Hospital Medan in 2023 - Donitha Rorescki Simanjuntak; Alexander P. Marpaung; Salomo G. U Simanjuntak; Dwi Lunarta D.S. Siahaan; Lesmana Syahrir (Jurnal Kedokteran Methodist, 2025)
Background : typhoid fever is an acute febrile disease caused by Salmonella typhi bacterial infection and can be caused also by Salmonella Paratyphoid a, Salmonella Typhi B, and Salmonella Paratyphoid C. Found endotoxin in bacterial polysaccharide S.typhi stimulate the production of cytokines and cause systemic symptoms such as fever, vomiting, headache, diarrhea, constipation. Endotoxins induce changes in bone marrow cells and affect ESR values and platelet counts. At the level of fever, there are 3 levels of temperature increase, namely febris, subfebris and hyperpyrexia. Objective: this study was conducted to determine the relationship of the value of ESR and platelet count to fever levels in pediatric patients with typhoid fever. Method: research method with observational analytical measurement through retrospective approach with cross sectional design, using secondary data in medical records, researchers make observations or measurements of variables at a particular time. Results : In the analysis there is a significant relationship between the value of the LED with fever level with a value of p=0.039 and there is no relationship between platelet count with fever level with a value of p=0.089. Conclusion: there is a relationship between the value of LED with fever level and there is no relationship between platelet count with fever level with a value of p= 0.089.